The Fifth Discussion on the Origin of the Universe (London Journal of Research In Science: Natural and Formal, 2024)
Humans are an amalgamation of matter and spirit (Liu, 2024.8a). They are a combination of the three- dimensional universe and the zero-dimensional universe (Liu, 2024.5). Humans have two origins: theorigin of the spirit and the origin of the body (Liu, “人类本原考”). The return to the origin of the spirit is called the death of the human body; the return to the origin of the body is called the death of the flesh. Humans are computer-like materials created by the universe, and the human spirit is software installed  by the universe. The existence and survival of humans are determined by the universe and by themselves.
Keywords: Hemodialysis; Chronic renal failure; protein-energy malnutrition; dietary habits.; Information.; Energy; matter; Origin of the Universe; Spirit; Body; Computer and Software; Software Programming